Biochar dari Limbah Tatal Karet Sebagai Media Filtrasi Pada Pengolahan Air Gambut - Anggrika Riyanti; Hadrah Hadrah; Riska Rahmah Dani Fitria (Jurnal Daur Lingkungan, 2023)
Biochar is a solid material formed from the carbonization of biomass. Biochar is the result of the conversion of organic waste by using the incomplete combustion method with a limited oxygen supply (pyrolysis). Meanwhile, the rubber scrap waste from the production of crumb rubber has not been utilized much other than as a mixture of fertilizer in the soil. This study aims to analyze the effectiveness of biochar as a peat water filtration media and the effect of biochar thickness on removal efficiency. Variations used are 100% biochar, 75% biochar – 25% silica sand, 50% biochar – 50% silica sand with three times repetation in each variation. with peat water test parameters are pH, color and organic matter (KMnO4). Parameters tested were pH, color and organic matter (KMnO4). The results showed that biochar was effective in neutralizing pH where the initial pH increased to 7.2, 4.2, color removal up to 75% and organic matter (KMnO4) up to 83%. The best variation is achieved at a ratio of 50% biochar – 50% silica sand. Variations that use 100% biochar actually provide lower removal efficiency. The combination of biochar with silica sand can further improve pollutant removal in filtration system.